2017
DOI: 10.1177/1203475417715208
|View full text |Cite
|
Sign up to set email alerts
|

Using Visual Aids to Enhance Physician-Patient Discussions and Increase Health Literacy

Abstract: Health literacy refers to the comprehension required to make well-informed decisions regarding one's health. It is a critical component in helping patients to understand how to take their medications appropriately. However, many patients do not possess the comprehension necessary for medication adherence. The result of poor literacy is a higher incidence of misunderstanding medication instructions. Visual aids have the ability to transcend language and numeracy barriers and can therefore improve the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Participants also suggested that patient education resources be available in formats which were easy to read and understand with illustrations to facilitate sensemaking. The evidence substantiates that utilising these formats for patient education resources are particularly effective, and have been shown to be superior to traditional methods of instruction (Houts et al 2006;Peregrin 2010;Pratt & Searles 2017;Verseput & Piccoli 2017).…”
Section: Implications For Practicementioning
confidence: 61%
See 1 more Smart Citation
“…Participants also suggested that patient education resources be available in formats which were easy to read and understand with illustrations to facilitate sensemaking. The evidence substantiates that utilising these formats for patient education resources are particularly effective, and have been shown to be superior to traditional methods of instruction (Houts et al 2006;Peregrin 2010;Pratt & Searles 2017;Verseput & Piccoli 2017).…”
Section: Implications For Practicementioning
confidence: 61%
“…Furthermore, carers also assisted with shopping and meal planning decisions. These findings suggest that to facilitate sensemaking for patients, it is important for dietetic services to be attentive to meeting the renal diet information needs of carers (Pratt & Searles ; Verseput & Piccoli ), by routinely inviting and involving them in education sessions (Hollingdale et al ). Specific carer training about the renal diet (such as cooking or meal preparation classes) may also be of use, because it may help to reduce carer burden and improve psychosocial outcomes for both patients and carers (Tong et al .…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Figure 1, low knowledge utilization would lead to more uncertainty. This information retention problem might be related to health literacy, which refers to the understanding that is needed to make well-informed decisions (Pratt & Searles, 2017). Previous authors have suggested that providing more detailed and clear information might be helpful, or else providing written information to improve the retention of information (Cahill et al, 2008;Hodge et al, 2013;Westervelt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have suggested that providing more detailed and clear information might be helpful, or else providing written information to improve the retention of information (Cahill et al, 2008;Hodge et al, 2013;Westervelt et al, 2007). Visual aids have also been shown to improve professional-patient discussions, information retention, and health literacy (Kessels, 2003;Pratt & Searles, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Pictorial resources and images can transcend literacy and numeracy barriers. 15 However, ensure images of people reflect the target audience and the physical abilities of those targeted. 16,17 PEMs that combine text with related illustrations increase recollection and comprehension.…”
Section: St Centurymentioning
confidence: 99%